Nutrition in the life cycle laboratory manual - Querubin, Milagros P. (Meriam & Webster Bookstore, 1994)
Purpose: "...designed to give an overview of nutrition principles in the management of diets for the at-risk groups of the population such as pregnant and lactating women; infants; pre-school and school-age children, teenagers, athletes and the elderly."